55 The use of breakout rooms and interaction to create a community of practice in a virtual learning environment. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Gallard, Sian; Rawlinson, Fiona; Griffiths, Jo; Harris, Dylan; Hayes, Jo; Grose, James; Richards, Jo
Abstract : Background/Introduction: Interaction and a community of practice are integral to postgraduate education. Previously, face to face (F2F) teaching allowed an opportunity for these factors to evolve naturally. Due to Covid -19 restrictions, this interaction needed to transition to virtual learning for a Palliative Medicine MSc. We explored the use of breakout room and use of a 'chat' function on a virtual learning platform to stimulate interaction and create a community of practice. These features were used within sessions for case based discussions, team building activities and immediate whole group responses to particular palliative care issues and challenges, enabling the cohort of students to build on each other's comments. Methods: Participants were invited to send immediate free-text evaluation of the sessions. These results were screened for comment on breakout rooms, and thematic analysis used to explore feelings towards this teaching strategy. Results: 252 responses were received across all sessions (45% response rate). Results were screened for reference to breakout rooms and use of the chat function. Thematic analysis revealed that these were positively received ('More breakout rooms', 'really good'), and gave rise to an opportunity for people to interact within a virtual learning environment. Additional unsolicited feedback to the course team indicated satisfaction with the delivery style ' 'I felt like there was still a really nice feeling of camaraderie, and that I got to know a lot of the others with the breakout rooms. I also felt much less inhibited using the chat function than I would putting my hand up in a lecture' Conclusions: Breakout rooms, and the use of the 'chat' function, were found to be an excellent medium with which to facilitate interaction and develop a community of practice. Using all aspects of technology to successfully support delivery of palliative care education can enhance palliative care knowledge during this time when F2F education is not possible.